Exploring neural network control for robot manipulator - Mokri, Siti Salasiah; Shafie, Amir Akramin; Mustaza, Seri Mastura (Penerbit Universiti Kebangsaan Malaysia, 2022)
Robot manipulators or robotic arms are extensively used in manufacturing sectors. Not just that, they are used in space exploration, military, robotic surgery, food industry among others. The main part of a robot manipulator is the arm that is used to handle or move an object. The basic form of robot manipulator is the single link manipulator. It is nonlinear due to gravitational force, load and posture. In addition, changes in rotor resistance and friction cause uncertainties. Thus, a good, flexible control for manipulator is a required. This book explores different neural network controls for single link manipulator and their performances are presented. The controllers are Neural Network Model Reference, NARMA L2 and Globally Linearizing with PID and Dynamic Neural Network.